Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T16:19:35+01:00
A {4-[-(-6) .(-3)+3]-13} .(-4)= {4-[-18+3]-13} .(-4)=(4+15-15).4= 16

b 0,2 .(-4)-0,2 .(-8)= -0,8+1,6= 0,8

c (-6) .0,28-0,24 .(-6)= -1,68+1,44= -0,24

d 4 .(-1/3) .(-1/3).(-5,6)=(4/9).(-5,6) = 2,4(8)

e (-5/8) .1,4 -1/4 .1,4= -0,875 - 0,35= 1,225

f 3/4 .(-0,6)- 0,6 .0,25= -0,45 - 0,15=0,6

g (-1,2) .1/3- (-2/3) .0,6= -0,4 +2/3=1,0(6)
1 5 1
2010-02-10T16:26:28+01:00
A) {4-[-(-6)*(-3)+3]-13}*(-4) = [4-(18+3)-13]*(-4) = [4-(-15)-13]*(-4) = 6*(-4)=-24
b) 0,2*(-4)-0,2*(-8)=-0,8-(-1,6)=0,8
c) (-6)*0,28-0,24*(-6)=-1,68-(-1,44)=0,24
d) 4*(-⅓)*(-⅓)*(-5,6)=-4/3*(-⅓)*(-5,6)=4/9*(-5,6)=2 i 22/45
e) (-5/8)*1,4-1/4*1,4=-7/8-7/20=-1,2
f) 3/4*(-0,6)-0,6-0,25=-9/20-9/20=-18/20=-0,9
g) (-1,2)*1/3-(2/3)*0,6=0,4-0,4=0
2 3 2